TEMPERATURE ACCLIMATION AND THE FATTY ACID COMPOSITION OF AN ANTARCTIC GREEN ALGA CHLORELLA (16th Symposium on Polar Biology) - ナガシマ, ヒデユキ; マツモト, ゲンキ; オオタニ, シュウジ; モモセ, ハルオ; NAGASHIMA, Hideyuki; MATSUMOTO, Genki I.; OHTANI, Shuji; MOMOSE, Haruo (National Institute of Polar Research, 1995)
P(論文) Antarctic green alga Chlorella vulgaris strain SO-26 cells cultured at 20℃ photosynthesize between 0-35℃, with a maximum rate at 20℃, while cells cultured at 10℃ show a shift of the optimum to about 2 to 3℃ lower and show higher activity than cells cultured at 20℃. Mesophilic alga Chlorella sorokiniana strain C-133 cells cultured at 20℃ photosynthesize between 5-45℃ with a maximum rate at 35℃, while cells cultured at 10℃ photosynthesize between 0-40℃ with a maximum rate at 30℃, in a temperature range about 5℃ lower than cells cultured at 20℃. Strain C-133 cells cultured at 20℃ show higher photosynthetic activity than cells cultured at 10℃. In both strains tested the major fatty acids are palmitic, linoleic and linolenic acids. When culture temperatures were changed from 20 to 10℃, the increase of the ratio of unsaturated fatty acid to total fatty acid in strain SO-26 was considerably greater than that in strain C-133. These results indicate that in photosynthesis the properties of an Antarctic Chlorella SO-26 are more psychrophilic than those of mesophilic Chlorella C-133, and both strains can be acclimated by the culture temperature, at least partly because of fatty acid unsaturation. departmental bulletin paper